Bank Risks, Shock Event and Profitability in Islamic Banks: Adoption of Panel Data Approach - Ahmad, Z; Ahmad, N; Syuhada Baharuddin, N (KnE Social Sciences, 2019)
In the current business environment banks are exposed to many risks while having its operation. These risks are stated to be directly linked to what banks do and why bank fails. The Islamic banks are also unexceptional to be affected by the bank risks. Thus, this study tries to examine the impact of bank risks and shock event in the variation of profitability in Islamic banks. Using 16 Islamic banks spanning from 2009 to 2016 in Malaysia this study has employed panel data analysis to test for the hypotheses. Results illustrated that there are substantial influence of both credit risks and liquidity risks credit risks on profitability in Islamic banks. Both shows the higher risks will lead to the lower profit of the Islamic bank. While, the shock event which is represented by financial crisis is found to be following the expected magnitude but has insignificant influences on the changes of Islamic bank profitability. This result gives a clear indication to Islamic banks that undertaking risks will let to the losses in the profitability of the banks. Finding also supports the claim that the profitability of Islamic banks is unharmed by the shock event. Keywords: Liquidity risks, Credit risk, Profitability, Islamic banks, financial crisis